Demographics and Clinical Outcomes of Patients Undergoing Anterior Cruciate Ligament Reconstruction with a Planned or Unplanned Hybrid Graft - Kraeutler, Matthew J.; Houck, Darby A.; Carver, Trevor J.; Bravman, Jonathan T.; Vidal, Armando F.; McCarty, Eric C. (The Journal of Knee Surgery, 2019)
The purpose of this study was to report the demographics and clinical outcomes of patients at our institution following anterior cruciate ligament reconstruction (ACLR) with a planned or unplanned hybrid autograft–allograft. At a minimum 2-year follow-up, patients at our institution who had undergone primary ACLR with a planned (P) or unplanned (U) hybrid graft using fresh-frozen allografts were contacted to complete a survey containing the Knee Injury and Osteoarthritis Outcome Score, Subjective International Knee Documentation Committee score, Single Assessment Numeric Evaluation, 12-Item Short Form Health Survey, and visual analog scale for activity level. Demographics were compared between groups. Patient-reported outcomes (PROs) and a revision rate were reported for each group. Mean follow-up among all patients was 3.3 years. Revision rate at follow-up was 0.8 and 6.3% in the P and U groups, respectively (p = 0.03). Among patients reached for follow-up (90 P, 30 U), a lower proportion of males was found in the unplanned hybrid graft group (P: 52%, U: 23%, p < 0.01). Unplanned hybrid graft patients were significantly younger at the time of surgery (P: 41.0 years, U: 31.0 years, p < 0.0001). Graft size did not differ between groups (P: 9.1 mm, U: 8.9 mm, p = 0.11). Patients in both groups achieved moderate to high PROs. Demographics differ between patients undergoing ACLR with a planned or unplanned hybrid graft. Patients with a planned hybrid graft are at a significantly reduced risk of postoperative graft failure, likely due to the older age of this group.
Keywords: anterior cruciate ligament reconstruction; hybrid graft; planned hybrid graft; unplanned hybrid graft